Partnership for scaling up gender and nutrition-sensitive CSA II (P4S II) - 2020 Regional Annual Report - Bayala, Jules; Chabi, Adéyèmi (World Agroforestry Centre, 2021)
Agriculture is the main source of livelihood of the majority of the people living in the West Africa (Sissoko et al. 2011). At the same time, African societies face growing global change risks, with rapidly changing patterns of human settlements and intensity of use of ecosystem services. In addition, climate variability and change has emerged as a major threat on agriculture, food security and livelihood of millions of people in this continent (IPCC, 2014) and particularly in Africa. Climate change and variability trends are worsening the stress on the ecosystems that ensure environmental security, both locally (e.g., ecosystem services), regionally (e.g., sustainable development options) and internationally (e.g., carbon sequestration). Several studies indicated that agriculture production could be significantly impacted due to increased temperatures, changed rainfall patterns, and more frequent and intense floods and droughts. In West-Africa region, agro-sylvo-pastoral production systems are mostly climate-dependent, and climate-related risks can cause severe losses of crop, forest and livestock production, the main livelihood activities of more than 80% of the population. In light of these constraints, more sustainable production systems, ensuring provision of the needs of current generations without jeopardizing those of future ones, are called for. In response, a more holistic approach, known as Climate-Smart Agriculture (CSA), is being developed, aiming at (i) sustainably improving productivity and income, (ii) adapting and building resilience to climate change and (iii) reducing and/or removing greenhouse gases emissions, where possible (FAO, 2010). There are many options to reduce the negative impacts of climate change on agricultural systems, make them resilient to climate change, and reduce emissions. Adopting Climate-smart agriculture (CSA) seems to be a suitable strategy to achieving food security while also mitigating and adapting to climate-related risks. In this perspectives, key elements include a comprehensive and gender-sensitive capacity development approach aligned with and driven by national priorities, applying knowledge management and effective learning approaches, facilitating multi-stakeholder processes, strengthening agricultural innovation systems and leveraging information and communication technologies (ICTs) and communication for development approaches FAO (2013). In line with the above, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) seeks to develop up-scalable options of CSA through improved understanding of mitigation and adaptation opportunities in agriculture among smallholders in West Africa. In 2015, ICRISAT and ICRAF signed a partnership agreement to implement the project “Building resilient agro-sylvo-pastoral systems in West Africa through participatory action research (BRAS-PAR). Merging the actions of BRAS-PAR and P4S I to become P4S II was done with the intention to use tools and evidence/lessons learned from the Climate-Smart Villages and other development activities, with existing and new partners through direct scientific support to decision makers (e.g., governments, civil society, and researchers) and capacity building to help bring CSA to scale. This project led by the World Agroforestry (ICRAF) and jointly implemented with the national research institutes in Burkina Faso, Senegal and Ghana, and the International Union for Conservation of Nature (IUCN) aims to develop up-scalable technological and social innovations of climate-smart agriculture integrating croplivestock-tree systems through improved understanding of farmer's perceptions and demands, by addressing barriers to adoption taking into consideration the gender and social differentiation. P4S also aims to providing CSA evidence and tools to key partners at the right time and in the right format to create a sea change in CSA implementation in Burkina Faso, Ghana and Senegal.